A Charging Strategy with the Price Stimulus Considering the Queue of Charging Station and EV Fast Charging Demand. (July 2018) - Yuan, Kai; Song, Yi; Shao, Yinchi; Sun, Chongbo; Wu, Zhili
Abstract: This paper proposes an electric vehicle (EV) charging guiding strategy with the price stimulus considering the queue of charging station and the EV fast charging demand. Firstly, a charging guiding framework based on the real-time information interaction is introduced. Secondly, the Origin-destination (OD) analysis is introduced to describe the distribution of EV fast charging demand. Based on the charging demand, a stack queue model is proposed to simulate the dynamic queue of EV charging stations, and a price stimulus method is adopted to guide the EV user to choose the charging station for minimizing the charging cost. Finally, a case is demonstrated to prove the effectiveness of the strategy.